(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Introduction: Ectopic pregnancy is a major clinical problem in gynaecology because it is often difficult to diagnose as the patient present in different ways. An accurate history taking and physical examination is considered to be most important in the diagnosis of ectopic pregnancy. There are two treatment options, medical or surgical. Surgical treatment is the fastest treatment for ectopic pregnancy though surgical management decreased from approximately 90% to 65%1. Surgery may be the only treatment option if there is internal bleeding. In the medical treatment group, 15% of cases were categorized as failures and required surgery1. Objectives: This study was conducted in the department of obst and Gynae of Dhaka Medical College Hospital from January 2005 to June 2005 in an attempt to find out the risk factors of ectopic pregnancy, the way of presentation and to analyze the operative treatment of ectopic pregnancy. Materials and Methods: A total 50 consecutive patients who were clinically suspicious of ectopic pregnancy were included in this study between January 2005 to June 2005. Patients who were clinically suspicious of EP and also supported by positive urinary pregnancy tests, beta hCG and no intrauterine gestational sac in ultrasonography were included in this study. Detailed discussion about the study was done with the patient and then informed verbal consent was taken from them. Detailed history about patient profile, presenting symptoms, any risk factors and clinical examination done and the findings were recorded in the predesigned data collection sheet. Data was expressed in terms of frequencies and percentages Results: Most of the patients were in the age group of 20-30 years and 38% of low parity (para- 1).Previous miscarriage, infertility,IUCD users and PID identified as the risk factors of ectopic pregnancy 42% patients had history of previous abortion or MR, period of infertility 22%, pelvic infection 12%, IUCD users 16%. In this study acute abdominal pain after a short period of amenorrhoea was found to be the main symptoms in ectopic pregnancy100% patients were presented with lower abdominal pain, 70% with period of amenorrhea and 50% patients with per vaginal bleeding. All the patients were presented with acute condition and were surgically managed fastest treatment. At the time of operation 84% of ectopic tubal pregnancy were found ruptured, 10% were tubal abortion and 4% unruptured. Sites of ectopic pregnancy were ampullary 50%, isthmic 20%, fimbrial 10%. Conclusion: Most of the patient presented in acute condition with the classical features of ruptured ectopic pregnancy. Near half of the patient were in younger age group (26 30 years) having risk factors like history of previous abortion/MR 42%, infertility 22% use of IUCD 16%, PID 12%. More then three forth( 84%) of cases were diagnosed as ruptured ectopic during operation. Operative management was done on the basis of site of ectopic and parity of the woman Bangladesh J Obstet Gynaecol, 2013; Vol. 28(1) : 9-14